Development of Edible Active Packaging Films from Natural Polyphenol Loaded Nanosolutions - Giridhara Rao, V.; Mallika, E. Naga; Rao, B. Eswara; Rao, T. Srinivasa (International Journal of Livestock Research, 2021)
The study was conducted to develop and evaluate alginate based active edible films with nanoemulsions of polyphenols. Films were developed using sodium alginate incorporating polyphenol nanosolutions of Quercetin and Tannic acid and their mechanical and physico-chemical parameters were compared. The film thickness and grammature ranged from 166.80 ± 2.84 to 199.45 ± 2.82 microns and 227.40 ± 3.42 to 255.23 ± 3.51 gm/m2 respectively which were significantly higher in Quercetin nanoemulsion incorporated films than Tannic acid nanosolution incorporated films and control (without nanoemulsion). The per cent elongation at break, tensile strength, opacity mean values were significantly higher in Tannic acid incorporated films than Quercetin incorporated films and control films. The water vapour permeability and water sorption values were found to be lower in Tannic acid nanosolution incorporated films whereas antioxidant activity, phenol content and antimicrobial activity of Tannic acid incorporated films were significantly higher than Quercetin incorporated films.